Ecology and management of grapevine leafroll disease - Almeida, Rodrigo; Daane, Kent; Bell, Vaughn; Blaisdell, G. Kai; Cooper, Monica; Herrbach, Etienne; Pietersen, Gerhard (Frontiers in Microbiology, 2013)
Grapevine leafroll disease (GLD) is caused by a complex of vector-borne virus species in the family Closteroviridae. GLD is present in all grape-growing regions of the world, primarily affecting wine grape varieties. The disease has emerged in the last two decades as one of the major factors affecting grape fruit quality, leading to research efforts aimed at reducing its economic impact. Most research has focused on the pathogens themselves, such as improved detection protocols, with limited work directed towards disease ecology and the development of management practices. Here we discuss the ecology and management of GLD, focusing primarily on Grapevine leafroll-associated virus 3, the most important virus species within the complex. We contextualize research done on this system within an ecological framework that forms the backbone of the discussion regarding current and potential GLD management strategies. To reach this goal, we introduce various aspects of GLD biology and ecology, followed by disease management case studies from four different countries and continents (South Africa, New Zealand, California-USA, and France). We review ongoing regional efforts that serve as models for improved strategies to control this economically important and worldwide disease, highlighting scientific gaps that must be filled for the development of knowledge-based sustainable GLD management practices.